A modest proposal for a new way forward for clinical research: Involve insurance companies. Issue 5 (9th February 2022) - Clark, James H.; Pinto, Jayant M.; Naclerio, Robert M.
Abstract: Is it time for medical insurance companies to organize and fund clinical research that evaluates the role of new treatments (drugs or device‐based therapies) in the context of existing clinical paradigms for common diseases?